MEASUREMENT OF THE SEPARATION FORCE OF THE DISC FROM THE LIQUID IN DISTANCE LEARNING CONDITIONS - Zdeshchyts, Valeriy; Zdeshchyts , Anastasia; Chеrnyсh Anastasia (Physical and Mathematical Education, 2022)
The method of remote laboratory work in physics is considered, which uses a self-made research installation to determine the functional dependence of the force of separation of the disk that touches the liquid with a flat surface, from the size of the disk area and its perimeter. Formulation of the problem. Jung’s equation connects the wetting angle and the coefficients of surface tension at the limit of the environments. It follows from this equation that the macroscopic parameter does not depend on the properties of molecules, and the idea of the force field between molecules is taken into account only on the line of their delimitation. Therefore, students erroneously conclude that the intermolecular force act only on the line of delimitation of environments. Thus, the implementation of laboratory work on the above topics solves this problem. Materials and methods. The goal: to determine the functional dependence of the separation force of the disk that touches the liquid with a flat surface from the size of the disk area, the presence of holes in it, and its perimeter - was solved by using a developed research installation. To measure the value of the separation force the lever method was used. Results. The dependence of the separation force from the perimeter of the disk (the line between the liquid and solid) was nonlinear and directly proportional to the wetted area. The coefficient of proportionality was ≈ 40 N / m2. Conclusions. 1) The force of separation of the disk from the water surface is disproportionate to the perimeter of the disk. This proves the fact that the surface tension of the fluid as a special real acting force does not express itself in this experiment. 2) The invariance of the value of the separation force of the same disk with an increasing number of holes made in it and the dependence of the separation force only on the surface area of the entire disk proves the fact that all the molecules contained in the contact layer of disk and liquid take part in holding the disk.